The Historical Development of the Tourism Criminal Law - KHSELLAT, Abdullah Al (Journal of Environmental Management and Tourism; Vol 12 No 8 (2021): JEMT, Volume XII, Issue 8(56), Winter 2021, 2021)
The significance of tourism is not limited to the movement of a person from one place to another for the purpose of leisure and travel, instead, tourism has become an independent industry like other industries, as there are many types of tourism such as medical, recreational, conference, study, and judicial tourism, in addition to the legal tourism, the meaning of which goes to define the concept of tourism and the tourist, which may lead to cross-border or interstate terrorist acts, and money laundering, and therefore a terrorist or money launderer cannot be considered a tourist. The article aims to highlight the existence of such tourism. At the same time, it made a presentation on the development of the criminal law of tourism in Jordan.